2012
DOI: 10.1016/j.joca.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Mice over-expressing salmon calcitonin have strongly attenuated osteoarthritic histopathological changes after destabilization of the medial meniscus

Abstract: sCT over-expressing mice had higher bone volume, and were protected against cartilage erosion. These data suggest that increased levels of sCT may hamper the pathogenesis of osteoarthritis (OA). However more studies are necessary to confirm these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
(41 reference statements)
3
25
0
Order By: Relevance
“…Administration of sCT significantly reduced CTX-2 levels in both SHAM and OVX animals 3 h after the final injection. This effect was greater in OVX animals, indicating that sCT may have protective effects on cartilage degradation, consistent with previous reports (Behets et al 2004, Bagger et al 2005, Sondergaard et al 2012. Administration of PTH in SHAM animals did not significantly alter CTX-2 levels, whereas in OVX animals PTH treatment significantly decreased CTX-2 levels.…”
Section: Resultssupporting
confidence: 90%
“…Administration of sCT significantly reduced CTX-2 levels in both SHAM and OVX animals 3 h after the final injection. This effect was greater in OVX animals, indicating that sCT may have protective effects on cartilage degradation, consistent with previous reports (Behets et al 2004, Bagger et al 2005, Sondergaard et al 2012. Administration of PTH in SHAM animals did not significantly alter CTX-2 levels, whereas in OVX animals PTH treatment significantly decreased CTX-2 levels.…”
Section: Resultssupporting
confidence: 90%
“…Further studies carried out in the canine Pond-Nuki model demonstrated that tiludronate exerts beneficial effects on gait disability and joint symptoms by improving some OA structural changes and reducing the synthesis of catabolic and inflammatory mediators [27]. Similar findings have been reported for calcitonin and estrogen use in different OA experimental models [16,[28][29][30][31][32][33][34][35][36][37][38][39][40]. Calcitonin prevented subchondral bone resorption and trabecular thinning associated to reduced cartilage degradation in a canine ACLT-induced OA model [28,29].…”
Section: Animal Studiessupporting
confidence: 65%
“…[48][49][50][51][52][53][54] In the DMM OA model on C57BL/6 mice, the DMM induced mechanical allodynia and activity obstacle coincidently with cartilage injury was found after 15 weeks of DMM surgery. Similar results also demonstrated by other groups, 26,39,55) but in their research, the slight pathological change on cartilage was found 9 weeks after the DMM surgery, different from 15 weeks in our DMM model.…”
Section: Discussionmentioning
confidence: 99%